Translanguaging in Singapore literary works and their translations: with scaffolds and strategies - Chang, Poh Joo (Nanyang Technological University, 2023)
This capstone project examines the conceptual framework of translanguaging and investigates how translanguaging can be practised in Singapore’s English and Chinese Literature and their respective translations. As Baynham & Lee (2019) noted, translanguaging research is done predominantly on spoken language. This paper thus aims to study how translanguaging can be applied to the written form, specifically in Singapore literary works and their respective translations. The study first investigates existing Singapore literary works to discover how translanguaging have already been practised in English and Chinese writings and translations. Some of these translanguaging techniques are then extrapolated and applied in my translation of a local English literary work, titled “17A Keong Saik Road”, written by Charmaine Leung. To translate the non-standard source languages (Chinese dialects, Malay and Singlish) that appeared throughout the ST, I reviewed the translation strategies compiled by Jing Yu in her 2014 study. In this study, Jing analysed a total of 202 Chinese translations to identify seven common translation strategies used to translate the English literary dialects (non-standard language) of three English literary works. I reconstructed five of these strategies and applied them on my ST. The translingual TT produced successfully captured and retained the subtle socio-cultural-linguistics nuances of the ST. To help readers bridge the linguistic and cultural gaps of this translingual TT, I followed the lead of Eriko Sato (2019) who proposed using scaffoldings, through the provision of ‘in-text clues’, to assist readers interpret any ‘foreign’ cultural terms in the TT. This effectively removed the need for out-of-text footnotes for this TT. I hope this project provides translators with some translanguaging and scaffolding strategies to produce reader-friendly translingual translations for multilingual literary works.